Analysis of Key Factors for the Growth of 99% Usahaku MSMEs Using Principal Component Analysis - Rany Aprilyanta; Fajar Sidiq Adi Prabowo (Universitas KH. Abdul Chalim Mojokerto, 2025)
The growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia plays a crucial role in supporting national economic development. Nevertheless, between 2017 and 2023, the progress of MSMEs has experienced fluctuations, even among those that are officially registered and supported by the 99% Usahaku platform. These inconsistencies are primarily due to ongoing challenges, particularly limited access to funding and technology. Given the definition and unique characteristics of MSMEs, this study seeks to examine whether there is a correlation between specific key factors and the growth of MSMEs listed on the 99% Usahaku platform. Furthermore, the research aims to identify which of these factors most significantly influence their growth. To achieve this, the study utilizes primary data collected via questionnaires distributed to 390 MSMEs, determined through the Slovin formula. The responses are analyzed using the SPSS statistical software, with Principal Component Analysis (PCA) serving as the primary method of analysis.The results, indicated by a KMO Measure of Sampling Adequacy (MSA) value of 0.586 (greater than 0.50) and a significant Bartlett’s Test of Sphericity (p-value < 0.05), suggest a meaningful correlation between the identified key factors and the growth of MSMEs on the 99% Usahaku platform, thus supporting the alternative hypothesis (H1). The analysis identifies thirteen key factors contributing to MSME growth on the platform: labor ecosystem, MSME ecosystem, competitive capacity, market operational ability, skilled human capital, business ecosystem, business information systems, digital adoption, organizational structure, market orientation, financial management, marketing competence, and operational support.